(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2025)
This paper presents an innovative approach to design and manufacture individualizable daily living aids for people with disabilities or motoric impairments. The focus is on enhancing autonomy in daily tasks through individualizable daily living aids that can be tailored to the user’s anatomy and limitations. Utilizing a combination of Additive Manufacturing (AM), parameterized design, and Artificial Intelligence (AI), a fully automated process chain was developed for individualizing and manufacturing these daily living aids. The process begins with a detailed product development, followed by the extraction of user-specific measurements from video or image data using AI-based image processing techniques. These measurements are passed on to a parametric design model, enabling quick adaptations to individualize the daily living aid. The result is a scalable process chain, where individualized daily living aids can be manufactured on demand, minimizing the need for standard solutions that may not meet the user’s needs. The case study focuses on a daily living aid for cutlery, demonstrating the successful integration of the developed process chain from design through production. The results highlight the potential of this automated process chain to improve the quality of life for people with disabilities, providing them with greater access to assistive devices tailored to their requirements.